THE EFFECT OF COMPENSATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PMKS PT. PADASA ENAM UTAMA KOTO KAMPAR HULU DISTRICT KAMPAR REGENCY - Ikhlas Satria; Zamhir Basem; Azhari Azhari (STIE Bangkinang Publishing, 2023)
Research to determine the effect of compensation and work discipline on employee performance with simulthan and partial at the PMKS PT. Padasa Enam Utama Koto Kampar Hulu District, Kampar Regency. Types and sources of data used in this study are primary data and secondary data, while data collection techniques used in this study were questionnaires, file research, observation and interviews. The population in this research were all employee at the PMKS PT. Padasa Enam Utama Koto Kampar Hulu District, Kampar Regency in 2020, amounting to 81 employee and all employee at the PMKS PT. Padasa Enam Utama Koto Kampar Hulu District, Kampar Regency were sampled so that the sampling technique in this research used a saturated census technique. Data analysis was performed using multiple linear regression models. Based on the simulthan test results, the variable of compensation and work discipline have a significant effect with together on the employee performance at PMKS PT. Padasa Enam Utama Koto Kampar Hulu District, Kampar Regency. While based on the partial test results, the variable of compensation and work discipline have a significant effect with individual on the employee performance at PMKS PT. Padasa Enam Utama Koto Kampar Hulu District, Kampar Regency. The closeness of the relationship that occurs between the atractiveness of compensation and work discipline on the employee performance is very strong with a correlation coefficient R of 80,2%. While contribution of independent variables to the dependent variables is equual to 63,4% while the remaining 36,6% is influenced by other variables not examined in this study.